Perfil epidemiológico de vítimas de feminicídio no estado do Amapá entre os anos de 2014 a 2018 - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Violence against women is a public health problem of great magnitude in the world, and its maximum expression is represented by femicide. Worldwide, in recent years, there has been an increasing trend in the rate of femicide, with Central America being the place with the highest occurrence. In Brazil, during the period 1980 to 2010, there has been a 100% increase in the femicide rate, which went from 2.3/100.000 to 4.6/100.000 women. Therefore, it is necessary to understand if there is a specific profile of women who suffer femicide, which would facilitate the identification and prevention of this act of violence. This research aimed to characterize the epidemiological profile of cases of femicide registered in the State of Amapá between the years 2014 to 2018. This is an observational, descriptive, retrospective, crosssectional study with a quantitative approach based on the database of the information service the Superintendence of Health Surveillance of the Ministry of Health, with mortality data, and the Scientific Police of Amapá, based on death certificates. For inferential analysis, the data were submitted to Pearson's chi-square test to assess the association between cause of death by ICD-10 group and epidemiological variables, using the SPSS 26.0 program, results being considered relevant with p≤0.05. During the study period there were 95 deaths of women due to aggression in Amapá, with an overall gross rate of 4.78 deaths per 100.000 women, this number after the second correction step rose to 126 deaths with a final global gross corrected rate of 6.34 deaths per 100.000 women. The epidemiological profile of women victims of femicide was a young woman, brown, with complete high school, single, student, resident in the capital, who died in the capital, in a hospital environment, without medical assistance, in October, on Sunday and Wednesday, in the afternoon shift and by firearm. There was an association between cause of death by ICD-10 group and age (p=0.012), municipality of residence (p=0.0001), municipality of occurrence (p=0.044), place of death (p=0.027), death way, if insidious and cruel (p=0.001). Although femicide has shown a decreasing in the State of Amapá, during the study period, the final corrected global gross rate is higher than the national average. The most frequent cause of death found was firearms, with a higher proportion in an isolated analysis of the capital. There is an evolution that occurs according to the facility's ease of having access to firearms. An important fact is the concentration of deaths on Wednesdays and Sundays, with the same days as the soccer games shown on brazilian television, where alcohol consumption is usually higher than usual, generating a propensity for violence and acts of cruelty. It is expected that with the characterization of this vulnerable population, more specific and effective measures can be taken to minimize the rates, in addition to stimulating further research to continue the information obtained, and thus influence the prevention of this heinous crime that affects mainly the economically active female population in Amapá.
Keywords: Mulher - Mortalidade; Mulher - Mortandade; Mulher - Violência; Feminicídio - Amapá; CNPQ::CIENCIAS DA SAUDE